Endo- and ectoparasites of large whales (Cetartiodactyla: Balaenopteridae, Physeteridae): Overcoming difficulties in obtaining appropriate samples by non- and minimally-invasive methods. Issue 3 (December 2015) - Hermosilla, Carlos; Silva, Liliana M.R.; Prieto, Rui; Kleinertz, Sonja; Taubert, Anja; Silva, Monica A.
Abstract: Baleen and sperm whales, belonging to the Order Cetartiodactyla, are the largest and heaviest existent mammals in the world, collectively known as large whales. Large whales have been subjected to a variety of conservation means, which could be better monitored and managed if physiological and pathophysiological information, such as pathogen infections, could already be gathered from free-swimming animals instead of carcasses. Parasitic diseases are increasingly recognized for their profound influences on individual, population, and even ecosystem health. Furthermore, a number of parasite species have gained importance as opportunistic neozoan infections in the marine environment. Nonetheless, traditional approaches to study parasitic diseases have been impractical for large whales, since there is no current routine method for the capture and handling of these large animals and there is presently no practical method to obtain blood samples remotely from free-ranging whales. Therefore, we here not only intend to review the endo- and ectoparasite fauna of large whales but also to provide new insights in current available methods for gathering parasitological data by using non- or minimally invasive sampling techniques. We focus on methods, which will allow detailed parasitological studies to gain a broader knowledge on parasitoses affecting wild, free-swimming large whale populations. Graphical abstract: Highlights: Endo- and ectoparasite fauna of free-ranging large whales. Overcoming difficulties in obtaining appropriate parasitological sample collection. Non- and minimally-invasive methods.